SÍNTESE E CARACTERIZAÇÃO VIBRACIONAL DE PEROVSKITAS COMPLEXAS COM ESTEQUIOMETRIA A(Ni⅓B"⅔)O₃ com A= Ca²⁺, Sr²⁺, Ba²⁺; e B"= Nb⁵⁺, Ta⁵⁺ - Barbosa, Diego Augusto Batista (2011)
In this work, we performed the synthesis of complex perovskites with stoichiometry A(Ni⅓B"⅔)O₃ with A= Ca²⁺, Sr²⁺, Ba²⁺ and and B"= Nb⁵⁺, Ta⁵⁺ ceramic method with grinding steps at low energies. Then, X-ray diffraction is performed to identify the phases obtained via characteristic diffraction profile, as well as possible extra phases and contaminations. The refinement of the diffraction pattern obtained is carried out through the Rietveld Method to obtaining crystallographic parameters of the desired phases and also estimate the masses of the same in relation to possibles extra phases, thus allowing a qualitative evaluation to the synthesis process. Subsequently, we performed Group Theory for the samples followed by the vibrational characterization of these perovskites via Confocal Raman microscopy which led, through literature review, to the observed modes identification and classification including modes activated by 1:2 ordering.